Penerapan Composite Performance Index untuk Rekomendasi Pemilihan Saham berbasis Aplikasi Penunjang Keputusan - Novita Br Ginting; Noor Syarif, Zulkarnaen; Jaenuddin, Jejen; Virgiawan, Rivaldi (Jurnal Etnik: Ekonomi-Teknik, 2024)
A website-based decision support information system for stock selection recommendations is an effort to help stock investors in Indonesia. The Composite Performance Index (CPI) method is a method that can rank (outranking) the final results. This method is also equipped to resolve cases with multiple criteria. The calculation criteria are stock financial ratios, which describe the company's financial performance during a specific period. The types of criteria used are Price to Book Value (PBV), Price to Earning (PER), Debt to Equity Ratio (DER), and Return on Equity (ROE). This research shows that the developed stock recommendation system can produce appropriate stock recommendations to help investors make investment decisions.